Improving Elementary School Teacher Competency Through Portfolio Assessment in Low Grade - Hamid Darmadi (Universitas Tanjungpura, 2020)
The purpose of this study was to obtain objective information and clarity regarding Elementary School Teacher Competitions through Low grade Portfolio Assessment. The results of this study indicated that the development of thematic learning models through the assessment of low-grade portfolio by Bengkayang District Elementary school teachers is in a